2-Imino-2, 3-dihydrobenzoxazole—a useful platform for designing rare- and alkaline earth complexes with variable di- and trianionic O, N, N, ligands. Issue 5 (14th January 2022) - Basalov, Ivan V.; Kissel, Alexander A.; Nikolaevskaya, Elena N.; Druzhkov, Nikolai O.; Cherkasov, Anton V.; Long, Jérôme; Larionova, Joulia; Fukin, Georgy K.; Trifonov, Alexander A.
Abstract : Yb(iii ), Y(iii ) and Ca(ii ) complexes coordinated by di- and trianionic diiminophenolate ligands. Abstract : The reactions of 2-imino-2, 3-dihydrobenzoxazole LH with M[N(SiMe3 )2 ]2 (THF)2 (M = Yb and Ca) and Y(CH2 SiMe3 )3 (THF)2 proceed with the opening of the dihydrobenzoxazole ring and the elimination of HN(SiMe3 )2 or SiMe4 . Besides, in the case of Yb[N(SiMe3 )2 ]2 (THF)2, an electron transfer from Yb(ii ) to L takes place and Yb(iii ) complex 1 is coordinated by a dianionic phenolate ligand containing a pendant radical-anionic diazabutadiene fragment form. When LH is reacted with Ca[N(SiMe3 )2 ]2 (THF)2, C–H bond activation of a methyl fragment by imino nitrogen occurs and affords a dimeric calcium complex 2 . In 2, the phenolate ligand is dianionic due to the presence of the amido-imino fragment [R–N{C(CH3 )–C({CH2 )–NR′] − (R = 2, 4- t Bu2 -C6 H2 O; R′ = 2, 6-iPr2 C6 H3 ). In situ generated ate-complex Na(Et2 O) n Ca[N(SiMe3 )2 ]3 also enables C–H bond activation, however the dianionic phenolate ligand in the resulting complex 3 contains an amido-imino fragment [R–N–C({CH2 )–C(CH3 ){NR′] − featuring the sequence of N–C and N{C bonds opposite to that in 2 . The reaction of Y(CH2 SiMe3 )3 (THF)2 with LH affords mono(alkyl) yttrium complex 4 . 4 contains a dianionic amido-imino phenolate ligand resulting from the migration of one alkyl group to the C{N bond [R–N–C(Me)(CH2 SiMe3 )–C(Me){NR′]. 4 undergoes slow intramolecular C–H bond activation of the residual CH3 group to afford a yttrium complex coordinated by a trianionic diamido-phenolate ligand [R–N–C(Me)(CH2 SiMe3 )–C({CH2 )NR′].